2020
DOI: 10.3847/1538-4357/ab5f0e
|View full text |Cite
|
Sign up to set email alerts
|

A Variant Stellar-to-nebular Dust Attenuation Ratio on Subgalactic and Galactic Scales

Abstract: The state-of-the-art geometry models of stars/dust suggest that dust attenuation toward nebular regions (A V,gas ) is always larger than that of stellar regions (A V,star ). Utilizing the newly released integral field spectroscopic data from the Mapping Nearby Galaxies at Apache Point Observatory survey, we investigate whether and how the A V,star /A V,gas ratio varies from subgalactic to galactic scales. On a subgalactic scale, we report a stronger correlation between A V,star and A V,gas for more active H ii… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 122 publications
5
15
0
Order By: Relevance
“…At the lowest density, log 10 Σ Hα 38.5, the stellar attenuation is stronger than the gas attenuation, mainly because of the small amount of dust in the gas as seen from the rapid decrease of E(B − V ) gas in the low-density end. The negative correlation of E(B − V ) star /E(B − V ) gas with Σ Hα has recently been discussed in depth in Lin & Kong (2020), based on an earlier sample of MaNGA. Our results show in addition that the correlation is essentially a result of the dichotomy of the intrinsic properties of the ionized gas regions, Hii regions and DIG regions, divided at Σ Hα ∼ 10 39 erg s −1 kpc −2 as suggested by Zhang et al (2017).…”
Section: Correlations Of Dust Attenuation With Regional/global Proper...mentioning
confidence: 95%
See 2 more Smart Citations
“…At the lowest density, log 10 Σ Hα 38.5, the stellar attenuation is stronger than the gas attenuation, mainly because of the small amount of dust in the gas as seen from the rapid decrease of E(B − V ) gas in the low-density end. The negative correlation of E(B − V ) star /E(B − V ) gas with Σ Hα has recently been discussed in depth in Lin & Kong (2020), based on an earlier sample of MaNGA. Our results show in addition that the correlation is essentially a result of the dichotomy of the intrinsic properties of the ionized gas regions, Hii regions and DIG regions, divided at Σ Hα ∼ 10 39 erg s −1 kpc −2 as suggested by Zhang et al (2017).…”
Section: Correlations Of Dust Attenuation With Regional/global Proper...mentioning
confidence: 95%
“…Similar to [Nii]/[Sii], the [Oiii]/[Oii] also shows no correlation with the stellar attenuation, but a strong correlation with the gas attenuation (see Figure 13). Both [Nii]/[Sii] and [Oiii]/[Oii] have been used as indicators of the ionization level of gas (Dopita et al 2013;Lin & Kong 2020). In the ionization model of spherical Hii regions from Dopita et al (2013), the line ratio of [Oiii]/[Oii] increases as the ionization parameter (q) increases, when the gas-phase metallicity diagnostics (e.g.…”
Section: Correlations Of Dust Attenuation With Regional/global Proper...mentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, we simply attribute non-AGN ionized gas to star-forming regions. However, such ionized gas also might have a nonnegligible contribution from DIG, which might be excited by mechanisms other than star formation, such as hot, low-mass evolved stars (Flores-Fajardo et al 2011;Zhang et al 2017) or shock (see Haffner et al 2009 for a review), and have a significant contribution to a sample of star-forming regions selected from the MaNGA survey (Lin & Kong 2020). DIG-dominated spaxels might not support the assumptions adopted in this work.…”
Section: Effect Of Diffuse Ionized Gasmentioning
confidence: 88%
“…The second argument allows us to use nebular attenuation derived from the Balmer decrement to trace the stellar attenuation. Previous works showed that the color excesses derived from emission lines and stellar continuum are correlated with each other in either galactic (e.g., Calzetti 1997) or subgalactic (e.g., Kreckel et al 2013;Lin & Kong 2020) star-forming systems. Therefore, one can use τ B to represent the relative reddening of of stellar continuum.…”
Section: Basic Ideamentioning
confidence: 99%